POSSIBILITIES OF APPLICATION OF COGNITIVE-BEHAVIORAL COACHING IN THE EDUCATION SYSTEM - Koc, Remigiusz (The Modern Higher Education Review, 2021)
The author raises the question of the possibility of using one of the coaching methods, which is cognitive-behavioural coaching, within the education system. The first part presents an analysis of the very concept of coaching, including research on its effectiveness in solving selected problems or improving selected areas / problems of the education system. In the further part, the author approaches and defines one of the types of coaching, that is cognitive behavioural-coaching. He cites the research on the effectiveness of this method, indicating the potential areas of its application in the education system. In order to demonstrate the potential usefulness of the cognitive-behavioural coaching method, the author refers to examples of techniques of working with a client (student, parent) derived from cognitive-behavioural therapy, which, in the author’s opinion, can be successfully transferred to the ground of cognitive-behavioural coaching. The article is exploratory in nature. The author raises the question of the application of cognitive-behavioural coaching in educational institutions, at the same time attracting attention to the need for in-depth empirical research in this area.